1990
DOI: 10.1073/pnas.87.16.6136
|View full text |Cite
|
Sign up to set email alerts
|

Priming of CD4+ T cells specific for conserved regions of human immunodeficiency virus glycoprotein gp120 in humans immunized with a recombinant envelope protein.

Abstract: A nonglycosylated denatured form of human immunodeficiency virus (HIV) 1 glycoprotein gpl20 (Env 2-3), which does not bind to CD4, was used with muramyl tripeptide as adjuvant to immunize HIV-seronegative healthy volunteers.In all the volunteers, three 50-,ug i 'ections of Env 2-3 induced priming of CD4+ T cells specific for conserved regions of the native glycosylated gpl20. Moreover, we found that several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…27). These released retrovirus-like structures can be purified in sucrose density gradients and can potentially be used for immunization (420 (4,201,255,394,592,870,926,1290). Most recent studies with a muramyl tripeptide (MTP)-based vaccine (see Section XXX F) containing the glycosylated gpl20 from the HIV-1sF2 strain have given encouraging results; relatively high levels of neutralizing antibodies and cellular immune responses were observed in human volunteers (533).…”
Section: Viral Coresmentioning
confidence: 99%
“…27). These released retrovirus-like structures can be purified in sucrose density gradients and can potentially be used for immunization (420 (4,201,255,394,592,870,926,1290). Most recent studies with a muramyl tripeptide (MTP)-based vaccine (see Section XXX F) containing the glycosylated gpl20 from the HIV-1sF2 strain have given encouraging results; relatively high levels of neutralizing antibodies and cellular immune responses were observed in human volunteers (533).…”
Section: Viral Coresmentioning
confidence: 99%
“…85 It has been demonstrated that glycosylation is critical for the Env-CD4 interaction, since non-glycosylated Env protein (env2-3) does not bind to CD4. 86,87 Thus, carbohydrate moieties on Env appear to provide a functional conformation to Env critical for its interaction with CD4. In addition, based on the crystallization studies of gp120, it appears that the exposed face of gp120 is heavily glycosylated (Fig.6A).…”
Section: Cd4 Inducible (Cd4i) Conformational Epitopes In Gp120mentioning
confidence: 99%
“…After 10 days, TCLs were cloned, by limiting dilution (0.3 cells/wells), in the presence of irradiated (30 Gy) allogeneic PBMCs, phytohemagglutinin (PHA-L 8 g/mL; Boehringer Mannheim, Mannheim, Germany), and rIL-2 (200 U/mL), using a previously described method. 35 As a control, CA-or HCMV-specific T-cell clones (TCCs) were also prepared from PBMCs of 3 healthy immunocompetent adult volunteers (control nos. 17, 18, and 19), who had previously encountered both antigens.…”
Section: Antigen-specific T-cell Lines and T-cell Clonesmentioning
confidence: 99%